Dyslexia, literacy and inclusion : child-centred perspectives - MacBlain, Sean; Long, Louise; Dunn, Jill (Lecturer in education) (Thousand Oaks, CA : Sage Publications, 2015)
This book is about raising standards in literacy for children with dyslexia by putting the child at the centre of everything you do, focusing on wellbeing, and recognising the role that adults have to play in ensuring all children reach their potential. Concentrating on children in primary schools and early years settings the book looks at: *Early intervention *Pupil voice *Working as a team *New literacies *Child-centred identification, assessment and provision *Challenges for the inclusive school. Suitable for all those working with children with dyslexia this book contains strategies that can be easily adopted to academically and emotionally benefit the children you are working with.
Description based on MARC record for print version.
Keywords: Language disorders in children